Perlindungan Anak Dalam Lapas: Peningkatan Fasilitas Dan Peran Staf - Harahap, Muhammad Alwi; Subroto, Mitro (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2023)
This article addresses a crucial issue in the criminal justice system, namely the protection of children in prisons. The main focus of this article is on improving facilities in prisons and the role of staff in maintaining and improving the protection of these marginalized children. In this context, the authors will discuss the standards of separation of children and adults, the education and guidance of children in prison, the protection of children's psychological well-being, and the role played by families and communities in maintaining the protection of these children. This article aims to provide a better understanding of how child protection in prisons can be improved through improved facilities and the active role of prison staff.